Effect of baker’s yeast fermented moist feed on the growth and bone mineralization in broiler - Aktar, Jesmin; Islam, Khan Md Shaiful; Chowdhury, Rakhi; Debi, Momota Rani; Emon, Ashik Iqbal (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: The effect of feeding yeast-fermented feed in various forms on broiler growth performance and bone mineralization was studied. Materials and Methods: Initially, a corn-soy-based diet was formulated and fermented in anaerobic conditions at 28°C in laboratory space for 48 h with yeast (2.0%) and moisture (50%). Afterward, the 150 newly hatched Arbeor Acres commercial broiler chicks were divided into 5 dietary groups (30 chicks, 6 cages, and 5 birds per cage). Each group received one of the following formulated and fermented diets: dry feed (DF), moist feed (MF), yeast-added dry feed (Y-DF), yeast-added moist feed (Y-MF), or yeast-fermented moist feed (YF-MF). Water and feed were supplied ad libitum. Six birds per group were slaughtered at age 37 for the determination of carcass traits and tibia ash. Results: Fermentation improved crude protein from 20.7% to 22.8% but declined crude fiber from 7.9% to 6.3% in the YF-MF group compared to the DF group. High body weight gain was recorded in 771, 830, and 992 gm in the MF, Y-MF, and YF-MF groups, respectively, compared to the DF (762 gm) group (p < 0.01). The feed conversion ratio was better in the Y-MF (1.57) and YF-MF (1.57) groups than in the DF (1.75) group. Feeding a fermented, moist diet resulted in improved carcass yield (69%) in the YF-MF group. Bone mineralization expressed a better tibia ash percentage (35% from 30%) in the YF-MF group compared to the DF group. Conclusion: Therefore, YF-MF enhanced the quality of feed and improved growth, carcass weight, and bone mineralization in broiler. Adv. Vet. Anim. Res., 11(1): 78-84, March 2024 http://doi.org/10.5455/javar.2024.k750